(3eYQaI eSGMI GdCTcGd GdcQjI hGdHSjWIs - ((3Hfj ehSi (B( (3eMeO hGdMSf hCMeOs
(3ChdgG (B:s
(3HYO GdOjHGLI UOQ GdcJGHI GdWhd hGdCbOGQ GdJi JMO GdCTcGd hgh eG GSJfO Ydi GSJbGeI ai GdLgJjf LejYkG aEfg jchf ef GdCWhd abW s
(3BNQgG (B:s
(3hcd eG hUafG ai cJGHfG aEfg ef YedfG GdGeYQaI GdeLSWj ef GdbWQ aEfg ef Yed GQTejOS s
(3Vef eLehY , JQJjHgG (B: 12s
(3HgG fXGe GdJYbjHIs
(3hHCNQI HQgGf BNQ Ydi GdTcd GdSGHY ef cJGH Hfi ehSjs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdj (B(1931) s
Keywords: (3eJaQbGJs